Health professional's willingness to advocate for strengthening global commitments to the Paris climate agreement: Findings from a multi-nation survey - Hye-ryeon Lee; Ian Pagano; Amanda Borth; Eryn Campbell; Benjamin Hubbert; John Kotcher; Edward Maibach (Elsevier, 2021)
Health professionals have the potential to address the health threats posed by climate change in many ways. This study sought to understand the factors that influence health professionals' willingness to engage in climate advocacy. We hypothesized and tested a model with six antecedent factors predicting willingness to engage in advocacy for strengthening global commitments to the Paris Agreement. Using survey data from members of health professional associations in 12 nations (n = 3,977), we tested the hypothesized relationships with structural equation modeling. All of the hypothesized relationships were confirmed. Specifically, higher rates of perceived expert consensus about human-caused climate change predicted greater climate change belief certainty and belief in human causation. In turn, all three of these factors, including higher levels of perceived health harms from climate change, positively predicted affective involvement with the issue. Affective involvement positively predicted the feeling that health professionals have a responsibility to deal with climate change. Lastly, this sense that climate advocacy is a responsibility of health professionals strongly predicted willingness to advocate. As a unique study of predictors of health professionals' willingness to advocate for climate change, our findings provide unique insight into how an influential set of trusted voices might be activated to address what is arguably the world's most pressing public health threat. Limitations of the study and suggestions for future research are presented, and implications for message development are discussed.